The world of mining - Jim Wark and others (CRC Press/Balkema, 2012)
"In this truly unique celebration of mining, breathtaking aerial photographs by award-wining photograpers Jim Wark and Richard Woldendorp accompany ground-level pictures of mines, mine-side oddities, and mine communities. Informed but breezy narratives by mining experts John Trudinger and Karlheinz Spitz identify and explain the images.The World of Mining shows that mining and associated activities can be impressive, attractive, and even spectacular. The book illustrates most if not all aspects of mining and mineral processing, in all its varieties, and from different environments throughout the world. It illustrates the colourful history of mining and its importance to the development of civilisation as we know it. It depicts the wide range of activities in modern mining, from exploration to mine closure, as well as traditional mining by skilled practitioners, using methods adapted to local condions.A visual feast for anyone interested, with and without a background in the earth sciences or photography. Recommended as well as a primary and secondary school information source on the subject"--Provided by publisher.